Reintroducing the Concept of Complementarity into Psychology - Wang, Zheng; Busemeyer, Jerome (Frontiers in Psychology, 2015)
Central to quantum theory is the concept of complementarity. In this essay, we argue that complementarity is also central to the emerging field of quantum cognition. We review the concept, its historical roots in psychology, and its development in quantum physics and offer examples of how it can be used to understand human cognition. The concept of complementarity provides a valuable and fresh perspective for organizing human cognitive phenomena and for understanding the nature of measurements in psychology. In turn, psychology can provide valuable new evidence and theoretical ideas to enrich this important scientific concept.